Social and multimedia influence on endurance athletes’ preferred snack choices - Chan, Yein Tsin; Nik Shanita Safii,; Chan, Wen Li (Penerbit Universiti Kebangsaan Malaysia, 2017)
Snacks are required for athletes to fuel their higher demand of energy. Meanwhile, social influences and multimedia can affect the athletes’ choices of snacks. Social influences are divided into three categories: Compliance (sports dietitian/nutritionist & medical officer), Conformity (friend) and Obedience (parent & coach), while multimedia refers to internet, magazines and newspaper. The objective of this study was to investigate the different sources of social influence and multimedia on athletes’ preferred snacks. Out of 26 snack choices, 3 most preferred snacks were chosen by 69 endurance athletes from the National Sports Institute (NSI) through a questionnaire. They are Popiah & Mixed Fruit Jelly, Chicken Salad and Egg & Cheese Sandwich. Out of the 6 choices of beverages, the top 3 preferred beverages were sports drinks, orange smoothie and apple smoothie. Social influence from parent (p = 0.041) has significant effect on the athlete’s most preferred snack choice, followed by influence from dietitian (p = 0.02) on their second preferred snack choice and lastly internet (p = 0.024), has its effect on the third preferred snack. Other social influences such as friends, medical officer and coach show no significance effect on the preferred snack choices. The parent factor also has significant effect on the most preferred beverage choices with p = 0.043. To conclude, parent influence is strongly related to both snack and beverage choices of the athletes, followed by dietitian and internet on the athlete’s preferred snack choices.